Aumento de gengiva queratinizada em mucosa peri-implantar - Almeida, Juliano Milanezi De [UNESP] (2012)
INTRODUCTION: Recent studies have evaluated the relationship between the width of keratinized mucosa and peri-implant tissue health. Insufficiently wide keratinized tissue can be increased surgically, for example by free gingival grafting. The presence or reconstruction of keratinized tissue around the implant can facilitate restorative procedures, promote aesthetics and allow the maintenance of an oral hygiene routine without irritation or discomfort to the patient. OBJECTIVE: To describe a patient who underwent free gingival graft surgery to increase the width of keratinized tissue in the region of previously implants to support a type of prosthetic protocol. CASE REPORT: A patient who had received dental implants to support a type of prosthetic protocol presented with inflamed peri‑implant mucosa, but with no keratinized tissue. Free gingival tissue was obtained from the palate and grafted into the anterior maxilla. Sixty days after muco-gingival surgery, we observed that the free gingival graft favored peri-implant health and prosthetic casting. CONCLUSION: The free gingival graft technique is both easy to perform and effective in increasing the width of keratinized mucosa following implantation.